Building a strategic perspective on the system of governance and measuring the level of its performance Survey study at the University of Basra - شبلي مسلم علاوي; منهل محمد حسين (Journal of Economics and Administrative Sciences, 2009)
The Local and Global Corporations are suffering of managerial and financial corruption phenomena, which leads them to loss and bankruptcy. So, it is necessary to search for tools which help prevent phenomena like this, and one of these tools is (corporate governance) which represent controlling tool that contribute in reducing corruption. this study aims at modifying (corporate governance system)in order to make it suitable with Iraqi government Corporations. the study depend upon main hypothesis which is (the performance level of the strategic perspective of governance system is depending upon work according to the perspective dimensions itself. From the main conclusions:-It is possible to building a strategic perspective of corporate governance for Iraqi government Corporations.